Field survey of symptoms and indications of Menstruation (Journal of the College of Basic Education, 2022)
A field survey was conducted among 2097 female unmarried, university-students, age from 19 to 22, from all levels of the society were interviewed from three Colleges.It appears that headache, lower abdominal ache, backache, temper, and digestive upsets are regular symptoms during the first five days precede the onset of menstruation. The pain increases gradually, but disappears in most cases by the fifth day according to their own statement.It appears, also, that the bleeding varies throughout the cycle. The commonest is the bleeding of the first and last two days (31.6%); psychological factors cause the irregularity of the cycle (57%). Side effects appear like diarrhea (12.6%), fainting (12.6%), and temporary paralysis (1.9%).Elder sisters were the mean source of information about the period followed by mothers. Only small percentage of the girls showed abnormal periods. The mean age of menarche was 12-13 years oldSelf-medications was practiced by the majority of the girls